Training on the Utilization of Local Microorganisms as Liquid Organic Fertilizer in Sungai Pangeran Village, Ilir Timur I District, Palembang City - Amir, Nurbaiti; Palmasari, Berliana; Fahmi, Innike Abdillah; Astuti, Dessy Tri (Altifani Journal: International Journal of Community Engagement, 2021)
Organic fertilizers are fertilizers that primarily consist of organic materials derived from plant or animal residues converted in solid or liquid form. Household waste, especially vegetable waste, is usually dumped directly into the environment, even though this waste can still be used, for example, made as liquid organic fertilizer by utilizing local microorganisms (MOL). The mole contains micro and macronutrients and contains bacteria that can decompose organic matter. This Community Service aims to provide motivation and knowledge, and skills to the community about the technique of making liquid organic fertilizer from household waste by utilizing local microorganisms. Community Service held in Sungai Pangeran Village, Ilir Timur I District, Palembang City, on February 19, 2019. The method used was counseling and training participants on the use of local microorganisms as liquid organic fertilizer. Thirty-five participants attended the implementation of the activity. This activity continued with discussions and questions and answers during the training. The results of this Community Service show that the service method in the form of counseling, training, and question and answer is very appropriate in motivating the community to remodel household waste.